A Performance Analysis of European Union Integration: The Prospects and Lessons for South Asia - Rasheed, Rukhsana; Nadeem, Mazhr; Imran, Muhammad (iRASD Journal of Economics, 2022)
This study captured the performance analysis of European Union (EU) member countries integration and its possible implications for South Asian countries. The primary purpose of this study was to see whether trading/economic bloc of EU has enhanced the performance of its members. The study also analyzed whether the European Union’s commercial bloc model can be proposed for other global regions. The data was collected from official sources of EU and it ranged from 2000 to 2021. Descriptive and inferential statistical methods have been applied for data analysis. The results showed that the EU trading groups have not only increased production but also increased the exports and welfare of the entire region of EU. On the basis of findings of this study, it may be suggested that South Asian countries (Sri Lanka, Pakistan, Bhutan, Nepal, Afghanistan, Bangladesh, India and Maldives) needs to construct a South Asian Trading Bloc, rather than SAARC, in order to boost the regional performance and well-being of concerned community.